Penciptaan Sejarah Makassar Di awal era modern / William Cummings; Penerjemah, Windu Yusuf; Penyunting, M. Nursam - CUMINGS, William; WINDU Yusuf; NURSAM, M (Penerbit Ombak, 2015)
xiv, 339 hlm. Illus. 20 cm.